2019
DOI: 10.1097/wnp.0000000000000579
|View full text |Cite
|
Sign up to set email alerts
|

Eye Movement Disorders and the Cerebellum

Abstract: Summary: The cerebellum works as a network hub for optimizing eye movements through its mutual connections with the brainstem and beyond. Here, we review three key areas in the cerebellum that are related to the control of eye movements: (1) the flocculus/paraflocculus (tonsil) complex, primarily for high-frequency, transient vestibular responses, and also for smooth pursuit maintenance and steady gaze holding; (2) the nodulus/ventral uvula, primarily for low-frequency, sustained vestibular responses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 75 publications
1
32
0
3
Order By: Relevance
“…1 B, corrected for multiple comparisons using family-wise error (FWE) cluster-wise correction. The following ROIs were significantly different between the BNC and CI groups: right cuneus, secondary visual cortex (V2), and left and right dorsal vermal region VI, which has been defined as the oculomotor vermis (OMV) 33 . The MNI coordinates which had the greatest T value and the uncorrected p -value per ROI were the following: right cuneus (MNI: 12x, − 80y, 28z) [t(74.3) = 3.95, p < 0.0001]; V2 (MNI: − 8x, − 76y, 0z) [t(85.5) = 5.20, p < 0.0001]; right vermal region VI (MNI: 6x, − 70y, − 16z) [(87.3) = 3.53, p < 0.0001]; and left vermal region VI (MNI: − 8x, − 68y, − 12z) [t(88.3) = 3.68, p < 0.001].…”
Section: Resultsmentioning
confidence: 99%
“…1 B, corrected for multiple comparisons using family-wise error (FWE) cluster-wise correction. The following ROIs were significantly different between the BNC and CI groups: right cuneus, secondary visual cortex (V2), and left and right dorsal vermal region VI, which has been defined as the oculomotor vermis (OMV) 33 . The MNI coordinates which had the greatest T value and the uncorrected p -value per ROI were the following: right cuneus (MNI: 12x, − 80y, 28z) [t(74.3) = 3.95, p < 0.0001]; V2 (MNI: − 8x, − 76y, 0z) [t(85.5) = 5.20, p < 0.0001]; right vermal region VI (MNI: 6x, − 70y, − 16z) [(87.3) = 3.53, p < 0.0001]; and left vermal region VI (MNI: − 8x, − 68y, − 12z) [t(88.3) = 3.68, p < 0.001].…”
Section: Resultsmentioning
confidence: 99%
“…Lesions inducing a pathologic, horizontal GEN are predominately located in the cerebellum (e.g. vermis, uvula, flocculus, tonsil) or the lower brainstem (vestibular nuclei, nucleus prepositus) [ 9 , 13 , 16 , 17 , 18 , 19 , 20 , 21 ]. Our results, as those in the literature, show that different lesions affect GEN and the location of the null point differently.…”
Section: Discussionmentioning
confidence: 99%
“…Lee [ 39 ] observed central positional nystagmus and spontaneous ocular volvulus in patients with lesions of the superior cerebellar feet. Shemesh [ 40 ] demonstrated that the damage to the posterior fastigial nucleus of the cerebellum decreased the accuracy of binocular saccade, and patients presented symptoms (such as dyslexia and blurred vision after changing the line of sight) and differences in binocular vision. The present study found that the esotropia showed a positive correlation with the VMHC values of the bilateral cerebellum crus 1 (r = 0.588; P < 0.05).…”
Section: Discussionmentioning
confidence: 99%